The use of antimicrobials in selective coliform media as a tool for quantifying resistant bacteria in aquatic ecosystems in Rio de Janeiro, Brazil - Gonçalves, Verônica Dias; Meirelles-Pereira, Frederico; Cataldo, Márcio; Esposto, Eglaise Miranda; Esteves, Francisco Assis; Guaraldi, Ana Luiza Mattos; Andrade, Arnaldo Feitosa Braga; Bello, Alexandre Ribeiro; Pereira, José Augusto Adler (Revista de Ciências Médicas e Biológicas, 2014)
Introduction: Water samples were collected from two areas of the Guanabara Bay, which suffered minor and major environmental degradation. Objective: To isolate the total coliforms (TC) and faecal coliforms (FC) present in the water and to determine the similarity of their multidrug-resistance profiles with the ones found in nosocomial bacteria. Material and Methods: A conventional and a modified most-probable-number (MPN) tests were performed in parallel. The modified test comprised the use of 8mg/ml of gentamicin in each set of EC and Lactose tubes and another set with 32mg/ml cephalothin. The differences on the MPN between the three sets of tubes was then determined. Results: The NMP found in both TC and FC were lower in the set of tubes containing gentamicin when compared with the set of tubes containing cephalothin nevertheless with an exception from the samples belonging to Guaxindiba river (minor environmental degradation area) and Mangue channel (major environmental degradation area) where the MPN of both TC and FC were higher in the set of tubes containing gentamicin. Conclusions: The results obtained in this study suggest that the modified MPN may be a promising technique to assist in the management of hydric resources. This study also raises the issue of wastewater treatment and disposal in hospitals, which have a high level of bacterial selective pressure, being discarded in the vicinity of the area studied here enabling animals and humans to be exposed to treatment challenging pathogenic bacteria.